KINERJA PENYULUH PERTANIAN LAPANGAN DI DESA PAHALETEN KECAMATAN KAKAS - Christian Meray; Olfie L.S. Benu; Gene H.M. Kapantow; Oktavianus Porajouw (Universitas Sam Ratulangi, 2014)
ABSTRACTCHRISTIAN H. Meray / 050314044, 2014. Performance Agricultural Extension Workers in Rural District of Kakas Pahaleten. Thesis. Under the guidance of Benu Olfie L.S, (Chair), Gene H.M Kapantow, (Member 1) and Oktavianus Porajouw, (Member 2).This study was conducted to determine the performance of agricultural extension field in the village of Kakas Pahaleten Subdistrict. It is expected that the results of this study may give an idea to obtain information as input to the government on the performance of Minahasa District agricultural extension so that its presence can be really helpful in improving the welfare of farmers.In the implementation of this study, respondents were taken as 1 extension and 7 farmers taken at random sampling from the three groups of farmers. This is done in order to determine the respondents obtained information from sources related to the purpose of this study.There are two factors that affect the performance of agricultural extension are internal factors that include age agricultural extension, education level, and years of agricultural extension while external factors include the availability of the necessary infrastructure, systems and shelter appreciation agricultural extension. Performance and success of agricultural extension is measured by 9 indicators: agricultural extension programs according to the needs of farmers, agricultural extension work plan in respective work areas - each, territory map data for location-specific technology development with region commodity, agricultural technology4dissemination evenly and according to the needs of farmers, empowerment and self-reliance of farmers and farmer groups, business partnerships between farmers and entrepreneurs are mutually beneficial, farmers' access to financial institutions of information and marketing of agricultural inputs, increase the productivity of agri-commodities on each seed - each work area, increase revenue and welfare of farmers in each region.The results of research on the performance of agricultural extension in the village of the District Kakas Pahaleten can be categorized either, as seen from the 9 indicators into the performance benchmarks extension plus the assessment of farmers to extension itself.